Locating battery supplying infrastructures for electric taxies. Issue 2 (7th February 2020) - Guo, Zhen; Yu, Bin; Li, Kewang; Yang, Yunong; Yao, Baozhen; Lin, Qingfeng
ABSTRACT: Vehicle electrification can help to decrease environmental pollution. But fast electricity consumption and inconvenient recharging service restrict the widespread adoption of electric vehicles, especially in the taxi industry. This paper attempts to solve a problem of locating battery supplying infrastructures for electric taxies. The problem involves the integration of two inter-related decision sub-problems: location optimization of charging centers, location optimization of battery-exchanging stations (BESs). To solve it, minimal cost model and corresponding algorithm are designed. Then, a case study of Dalian, China is conducted to show the effectiveness of our model and algorithm. Computational results can provide the government with good insight into how to realize taxi electrician and therefore contribute to the further planning of vehicle electrification system.